Hydrodemolition and drill and blast: A new way to improve tunnel contour quality - Rafael Pacheco dos Santos; Marcos Aurélio Marques Noronha; Patrícia de Oliveira Faria; Thiane Pereira Poncetta Coliboro (REM: International Engineering Journal)
Abstract Drill and Blast is one of the most utilized excavation methods due to its cost and adaptation capability. One undesirable feature, however, is the contour shape quality of the blasted cavity. It is usually larger and rougher than planned. This characteristic is related to the crack generated by blasting that propagates until it finds a discontinuity. Some methods for overbreak and roughness control are used but they are far from perfect. One option is to replace explosives with the High-Power Abrasive Water Jet (HPAWJ) Technique for rock cutting the perimeter; a necessary step before execution of the Pre-Splitting Technique. These two techniques can create one free surface, with good roughness, capable of avoiding the crack propagation during the blast process. In this article, through a qualitative comparative research, an adaptive cycle is proposed, based on Drill and Blast, that uses HPAWJ for cutting the perimeter. In addition to the improvement on the tunnel wall roughness, this change can reduce the excavation-damage zone and the overbreak, which leads to a reduction of the amounts of shotcrete and muck, consequently reducing the need for transportation.